Mitigating diseases transmitted by Aedes mosquitoes: a cluster-randomised trial of permethrin-impregnated school uniforms - Kittayapong, Pattamaporn; Louis, Valérie R.; Tozan, Yeşim; Wilder-Smith, Annelies (PLoS neglected tropical diseases, 2017)
Background Viral diseases transmitted via Aedes mosquitoes are on the rise, such as Zika, dengue, and chikungunya. Novel tools to mitigate Aedes mosquitoes-transmitted diseases are urgently needed. We tested whether commercially insecticide-impregnated school uniforms can reduce dengue incidence in school children. Methods We designed a cluster-randomised controlled trial in Thailand. The primary endpoint was laboratory-confirmed dengue infections. Secondary endpoints were school absenteeism; and impregnated uniforms’ 1-hour knock-down and 24 hour mosquito mortality as measured by standardised WHOPES bioassay cone tests at baseline and after repeated washing. Furthermore, entomological assessments inside classrooms and in outside areas of schools were conducted. Results We enrolled 1,811 pupils aged 6-17 from 5 intervention and 5 control schools. Paired serum samples were obtained from 1,655 pupils. In the control schools, 24/641 (3.7%) and in the intervention schools 33/1,014 (3.3%) students had evidence of new dengue infections during one school term (5 months). There was no significant difference in proportions of students having incident dengue infections between the intervention and control schools, with adjustment for clustering by school. WHOPES cone tests showed a 100% knock down and mortality of Aedes aegypti mosquitoes exposed to impregnated clothing at baseline and up to 4 washes, but this efficacy rapidly declined to below 20% after 20 washes, corresponding to a weekly reduction in knock-down and mosquito mortality by 4.7% and 4.4% respectively. Results of the entomological assessments showed that the mean number of Aedes aegypti mosquitoes caught inside the classrooms of the intervention schools was significantly reduced in the month following the introduction of the impregnated uniforms, compared to those collected in classrooms of the control schools (p = 0.04) Conclusions Entomological assessments showed that the intervention had some impact on the number of Aedes mosquitoes inside treatment schools immediately after impregnation and before insecticidal activity declined. However, there was no serological evidence of protection against dengue infections over the five months school term, best explained by the rapid washing-out of permethrin after 4 washes. If rapid washing-out of permethrin could be overcome by novel technological approaches, insecticide-treated clothes might become a potentially cost-effective and scalable intervention to protect against diseases transmitted by Aedes mosquitoes such as dengue, Zika, and chikungunya. Trial Registration ClinicalTrials.gov NCT01563640
Gesehen am 17.10.2018